MEKANISME CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - Nurul Alfian (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2019)
Implementationof good corporate governance can be considered as a way to improve the image of the bank declined, protect the interests of stakeholders and improve regulatory compliance to applicable law and ethics in the banking industry in improving the banking system is healthy. This research was conducted to examine the mechanism of corporate governance (managerial ownership, institutional ownership, and corporate audit committee) that affect the performance of financial statements. The research method use multiple linear regression analysis and the sampling technique use purposive sampling method. The results of this study present that there is a significant influence of managerial ownership, institutional ownership and corporate audit committee on financial performance.